2017
DOI: 10.1016/j.ajhg.2017.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Biallelic Mutations in CFAP43 and CFAP44 Cause Male Infertility with Multiple Morphological Abnormalities of the Sperm Flagella

Abstract: Sperm motility is vital to human reproduction. Malformations of sperm flagella can cause male infertility. Men with multiple morphological abnormalities of the flagella (MMAF) have abnormal spermatozoa with absent, short, coiled, bent, and/or irregular-caliber flagella, which impair sperm motility. The known human MMAF-associated genes, such as DNAH1, only account for fewer than 45% of affected individuals. Pathogenic mechanisms in the genetically unexplained MMAF remain to be elucidated. Here, we conducted ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
212
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 255 publications
(240 citation statements)
references
References 50 publications
11
212
0
Order By: Relevance
“…One is that the disruption of the CFAP65 gene caused by Rose‐comb mutation in chickens can lead to impaired sperm motility in male homozygotes . Another research detected a different homozygous nonsense mutation in CFAP65 (c.5341G>T; [p.Glu1781*]) in an infertile male with MMAF . Here, we identified the negative effect of the p.Trp892* mutation on CFAP65 expression and the sperm flagellar development.…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…One is that the disruption of the CFAP65 gene caused by Rose‐comb mutation in chickens can lead to impaired sperm motility in male homozygotes . Another research detected a different homozygous nonsense mutation in CFAP65 (c.5341G>T; [p.Glu1781*]) in an infertile male with MMAF . Here, we identified the negative effect of the p.Trp892* mutation on CFAP65 expression and the sperm flagellar development.…”
Section: Introductionmentioning
confidence: 63%
“…Since 2014, when MMAF was defined, studies have shown that mutations in genes associated with sperm flagellum development may lead to MMAF . Here, another candidate gene, CFAP65 , was identified in an infertile male with MMAF by WES.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Multiple studies have indicated that biallelic mutations in DNAH1, CFAP43 and CFAP44, which occur with a frequency that is independent of genetic origin, cause the majority of MMAF cases (Amiri-Yekta et al, 2016;Ben Khelifa et al, 2014;Sha et al, 2018;Sha, Yang, et al, 2017;Tang et al, 2017;Wang et al, 2017). Multiple studies have indicated that biallelic mutations in DNAH1, CFAP43 and CFAP44, which occur with a frequency that is independent of genetic origin, cause the majority of MMAF cases (Amiri-Yekta et al, 2016;Ben Khelifa et al, 2014;Sha et al, 2018;Sha, Yang, et al, 2017;Tang et al, 2017;Wang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple morphological abnormalities in the same patient's spermatozoa tail structure and ultrastructure which impair motility can show the mutation of some genes (DNAH1, DNAJB13, CFAP43 and CFAP44) [70][71][72][73].…”
Section: Spermatozoa -Facts and Perspectivesmentioning
confidence: 99%